2021
DOI: 10.20944/preprints202105.0344.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acceptability, Appropriateness, and Feasibility of Automated Screening Approaches and Family Communication Methods for Identification of Familial Hypercholesterolemia: Stakeholder Engagement Results from the IMPACT-FH study

Abstract: Guided by the Conceptual Model of Implementation Research, we explored the acceptability, appropriateness, and feasibility of: 1) automated screening approaches utilizing existing health data to identify those who require subsequent diagnostic evaluation for familial hypercholesterolemia (FH) and 2) family communication methods including chatbots and direct contact to communicate information about inherited risk for FH. Focus groups were conducted with 22 individuals with FH (2 groups) and 20 clinicians (3 gro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Understanding drivers of cascade testing and the impact of a combination of methods can inform efforts to improve accessibility to genetic testing and tailor clinical communication workflows. To explore these issues further, work refining the FST and cascade chatbot and reducing logistical barriers to cascade testing is underway as part of the NIH‐funded ‘Identification Methods, Patient Activation, and Cascade Testing for Familial Hypercholesterolemia’ (IMPACT‐FH) study at Geisinger (Campbell‐Salome et al, 2021; Jones et al, 2021). A primary goal of this multi‐aim, multiple method study centers on feedback from stakeholders (i.e., individuals and families with familial hypercholesterolemia and relevant clinicians) to improve cascade testing communication tools available to probands who have received familial hypercholesterolemia results and their relatives including a family letter, chatbot, and a direct contact program (Campbell‐Salome et al, 2021).…”
Section: Study Limitationsmentioning
confidence: 99%
“…Understanding drivers of cascade testing and the impact of a combination of methods can inform efforts to improve accessibility to genetic testing and tailor clinical communication workflows. To explore these issues further, work refining the FST and cascade chatbot and reducing logistical barriers to cascade testing is underway as part of the NIH‐funded ‘Identification Methods, Patient Activation, and Cascade Testing for Familial Hypercholesterolemia’ (IMPACT‐FH) study at Geisinger (Campbell‐Salome et al, 2021; Jones et al, 2021). A primary goal of this multi‐aim, multiple method study centers on feedback from stakeholders (i.e., individuals and families with familial hypercholesterolemia and relevant clinicians) to improve cascade testing communication tools available to probands who have received familial hypercholesterolemia results and their relatives including a family letter, chatbot, and a direct contact program (Campbell‐Salome et al, 2021).…”
Section: Study Limitationsmentioning
confidence: 99%
“…Findings from the current study complement this pilot genetic counseling intervention by providing examples of message features future interventions can incorporate to communicate about FH risk and motivate cascade testing uptake. Finally, individuals with FH and clinicians have expressed that innovative tools such as chatbots and direct contact of at-risk relatives by clinicians would be helpful ways for clinicians to facilitate family communication [ 20 ]. However, future research should investigate how clinicians’ influence may be moderated by the mode of communication used to interact with at-risk relatives.…”
Section: Discussionmentioning
confidence: 99%
“…At-risk relatives may perceive clinicians as credible and authoritative sources of information, which can better motivate at-risk relatives to pursue cascade testing [ 15 , 16 ]. Previous research has shown that communication methods from clinicians such as “Dear Family” letters [ 17 ], digital tools like chatbots [ 18 ], and direct contact programs [ 10 , 19 ] are acceptable to patients, families, and clinicians, and can be effective for identifying more individuals with FH [ 11 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%